Sex differences in the prevalence and clinical outcomes of subclinical peripheral artery disease in the Health, Aging, and Body Composition (Health ABC) study. (April 2014) - Hiramoto, Jade S; Katz, Ronit; Ix, Joachim H; Wassel, Christina; Rodondi, Nicolas; Windham, B Gwen; Harris, Tamara; Koster, Annemarie; Satterfield, Suzanne; Newman, Anne; Shlipak, Michael G
The objective of the study was to determine if there are sex-based differences in the prevalence and clinical outcomes of subclinical peripheral artery disease (PAD). We evaluated the sex-specific associations of ankle–brachial index (ABI) with clinical cardiovascular disease outcomes in 2797 participants without prevalent clinical PAD and with a baseline ABI measurement in the Health, Aging, and Body Composition study. The mean age was 74 years, 40% were black, and 52% were women. Median follow-up was 9.37 years. Women had a similar prevalence of ABI < 0.9 (12% women versus 11% men; P = 0.44), but a higher prevalence of ABI 0.9–1.0 (15% versus 10%, respectively; P < 0.001). In a fully adjusted model, ABI < 0.9 was significantly associated with higher coronary heart disease (CHD) mortality, incident clinical PAD and incident myocardial infarction in both women and men. ABI < 0.9 was significantly associated with incident stroke only in women. ABI 0.9–1.0 was significantly associated with CHD death in both women (hazard ratio 4.84, 1.53–15.31) and men (3.49, 1.39–8.72). However, ABI 0.9–1.0 was significantly associated with incident clinical PAD (3.33, 1.44–7.70) and incident stroke (2.45, 1.38–4.35) only in women. Subclinical PAD was strongly associated with adverse CV events in both women and men, but women had a higher prevalence of subclinical PAD.